Relational Wealth: Quantity and Quality of Interpersonal Relations - Rojas, Mariano (Springer Link, 2024)
The quantity and quality of interpersonal relations is an important driver of people’s well-being. Latin Americans’ high well-being levels can be explained by the abundance of close, warm and genuine interpersonal relations in all relational spheres of life. The quantity and quality of relations people have are independent of their economic condition; in other words; income does not buy good relations. Public policy should not assume that economic growth and higher income translates into better interpersonal relations; on the contrary, it is recommended for public policy to take into consideration the potential negative impact that some pro economic growth policies may have on the quantity and quality of interpersonal relations.
Keywords: relational wealth; interpersonal relations; quantity; quality; WOS(2)